Efficacy of photodynamic therapy with laser pretreatment for actinic keratosis and photorejuvenation as evaluated by fluorescent imaging. Issue 1 (4th November 2014) - Kim, Bo‐Kyung; Lee, Noo Ri; Park, Sang‐Yeon; Eom, Minseob; Choi, Eung Ho
Summary Background The Methylaminolevulinate‐photodynamic therapy (MAL‐PDT) has been reported to be effective in treating actinic keratosis (AK). Fluorescent images taken after topical MAL application have been used to diagnose cancerous lesions. Objectives We evaluated therapeutic efficacy of MAL‐PDT for multiple AK and defined value of fluorescent images in evaluating treatment response. We also investigated photorejuvenation effects of PDT. Methods Ten patients with multiple AK were enrolled. We did histological confirmation of the lesion by biopsy. After 3 h of MAL cream occlusion, red light was illuminated with 37 J/cm2 on 0, 4, 16, and 20 weeks. At each visit, lesions were counted by inspection and fluorescent images were taken under ultraviolet A light. We repeated skin biopsy in 16 weeks. Results All patients showed significant improvement after three sessions of PDT. The average remission rate was 85.96%. Overall, patients showed significant improvement in photoaging such as erythema, coarse wrinkles, and skin roughness. Histological examination also showed improvement. There was meaningful agreement between lesion count by fluorescent imaging and inspection (coefficient = 0.9). Conclusions PDT was found to be effective, well‐tolerated, cosmetically acceptable for AK treatment and photorejuvenation, both clinically and histologically. In addition, fluorescent images taken after MAL application aided in evaluation of treatment response as well as diagnosis.